Hirschsprung Disease beyond Infancy - Calkins, Casey M. (Clinics in Colon and Rectal Surgery, 2018)
Hirschsprung disease (HD) is a common cause of neonatal intestinal obstruction in which a variable segment of the distal intestinal tract lacks the normal enteric nervous system elements. Affected individuals present with varying degrees of obstructive symptoms, but today most patients are diagnosed within the first several months of life owing to the well-recognized symptoms and the ease of making the diagnosis by way of the bedside suction rectal biopsy. Thus, for the adult general or colorectal surgeon, the vast majority of patients who present for evaluation will have already undergone surgical treatment within the first year of life by a pediatric surgeon. Despite several safe operative interventions to treat patients with HD, the long-term results are far from perfect. These patients may reach adult life with ongoing defecation disorders that require a systematic evaluation by a multidisciplinary group that should be led by a surgeon with a thorough knowledge of HD operations and the potential problems. The evaluation of these patients will form the basis for the majority of this review—however, some patients manage to escape diagnosis beyond the infant and childhood period—and a section herein will briefly address the case of an older patient who is suspected of having HD.
Keywords: Hirschsprung; complications; reoperation; incontinence; constipation